Fuchs Endothelial Corneal Dystrophy: The Vicious Cycle of Fuchs Pathogenesis - Tone, Stephan Ong (Prog Retin Eye Res, 2020)
Fuchs endothelial corneal dystrophy (FECD) is the most common primary corneal endothelial dystrophy and the leading indication for corneal transplantation worldwide. FECD is characterized by the progressive decline of corneal endothelial cells (CECs) and the formation of extracellular matrix (ECM) excrescences in the Descemet’s membrane (DM), called guttae, that lead to corneal edema and loss of vision. FECD typically manifests in the fifth decades of life and has a greater incidence in women. FECD is a complex and heterogeneous genetic disease where interaction between genetic and environmental factors results in cellular apoptosis and aberrant ECM deposition. In this review, we will discuss a complex interplay of genetic, epigenetic, and exogenous factors in inciting oxidative stress, auto(mito)phagy, unfolded protein response, and mitochondrial dysfunction during CEC degeneration. Specifically, we explore the factors that influence cellular fate to undergo apoptosis, senescence, and endothelial-to-mesenchymal transition. These findings will highlight the importance of abnormal CEC-DM interactions in triggering the vicious cycle of FECD pathogenesis. We will also review clinical characteristics, diagnostic tools, and current medical and surgical management options for FECD patients. These new paradigms in FECD pathogenesis present an opportunity to develop novel therapeutics for the treatment of FECD.